2022
DOI: 10.48550/arxiv.2202.10043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergence of Discontinuous Galerkin Schemes for the Euler Equations via Dissipative Weak Solutions

Abstract: In this paper, we present convergence analysis of high-order finite element based methods, in particular, we focus on a discontinuous Galerkin scheme using summation-by-parts operators. To this end, it is crucial that structure preserving properties, such as positivity preservation and entropy inequality hold. We demonstrate how to ensure them and prove the convergence of our multidimensional high-order DG scheme via dissipative weak solutions. In numerical simulations, we verify our theoretical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Proof. The proof follows analogous steps as presented in [30,36]. It uses the fact that the RD schemes with the MOOD approach lead to consistent and stable approximation of the Euler equations.…”
Section: Convergence To Dissipative Weak Solutionsmentioning
confidence: 95%
See 3 more Smart Citations
“…Proof. The proof follows analogous steps as presented in [30,36]. It uses the fact that the RD schemes with the MOOD approach lead to consistent and stable approximation of the Euler equations.…”
Section: Convergence To Dissipative Weak Solutionsmentioning
confidence: 95%
“…At all, we demonstrated that our final implemented scheme is high-order, structure preserving and consistent. These are exactly the properties which are needed to prove a convergence result in the spirit of [28,29,37,36]. We start with the weak convergence theorem similar to [36].…”
Section: Convergence To Dissipative Weak Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensions to multiphase flows are as well planned. Finally, our high-order FV blending schemes can be also the starting point of a convergence analysis for the Euler equations via dissipative measure-valued solutions [17,34] which is already work in progress.…”
Section: Testing Of Thementioning
confidence: 99%